Government expenditure in the DINA framework: Allocation methods and consequences for post-tax income inequality - Lukas Riedel; Holger Stichnoth (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Constructing measures of post-tax income inequality that are consistent with national accounts requires the allocation of the entirety of government expenditure to individuals. About half of government expenditure in the United States takes the form of in-kind collective expenditure (e.g., education, defense, infrastructure). The dominant assumption in the literature is to allocate this expenditure proportionally to post-tax cash income. We show that the gap in post-tax income shares between the Top 10% and Bottom 50% in the United States is reduced by half (from about 20 to 10 percentage points in recent years) when this assumption is replaced by a lump-sum allocation. We further provide direct evidence on how a substantial part of collective expenditure is actually distributed. When adopting the cross-sectional perspective of the Dina approach, we find that public education spending goes disproportionately to the bottom half of the income distribution. A lump-sum allocation provides a good approximation. Moving beyond the cross-section, we find that public education expenditure is positively correlated with both lifetime earnings and parents' socio-economic status.
Keywords: D31; H41; H52; I24; 330; inequality; redistribution; education; in-kind transfers